The solution of (3x - 1)/5 - (1 + x)/2 = 3 - (x - 1)/2 is (A) 5 (B) -7 (C) 7 (D) -5

Given

(3x – 1)/5 – (1 + x)/2 = 3 – (x – 1)/2

(3x – 1)/5 – (1 + x)/2 + (x – 1)/2 = 3

On taking LCM, we get,

(6x – 2 – 5 – 5x + 5x – 5)/10 = 3

(6x – 12)/10 = 3

6x – 12 = 30

6x = 30 + 12

6x = 42

x = 42/6

We get,

x = 7

Hence, the correct option is (C)

Was this answer helpful?

 
   

0 (0)

(0)
(0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question